Exploration of Organisational Culture and Motivation in Improving Employee Performance: A Case Study on Service Companies in Indonesia - Abdul Kodir Djaelani; Moh. Cholid Mawardi (Pusat Riset dan Inovasi Nasional, 2025)
Employee performance in service companies in Indonesia is often hampered by less than optimal organisational culture and work motivation, which impacts on the productivity and competitiveness of the company. This study aims to explore the influence of organisational culture and work motivation on employee performance in service companies in Jakarta. The method used is a quantitative survey with a Structural Equation Modeling (SEM) approach using AMOS, involving 120 respondents selected by purposive sampling. The results of the analysis show that organisational culture and work motivation simultaneously have a positive and significant effect on employee performance, with work motivation having a more dominant influence. This finding strengthens human resource management theory regarding the importance of integrating organisational culture and motivation in improving performance. The practical implication of this study is the need to develop a holistic management strategy to strengthen organisational culture and increase work motivation to encourage optimal employee performance in the service sector. This research also opens up opportunities for further studies with a mixed methods approach and mediating variables to enrich the understanding of human resource dynamics in Indonesia.